Disaster management: Identifying Malaysian nurses’ knowledge and predictor factors - Ahayalimudin, Nurul'Ain; Ismail, Aniza; Mohd Saiboon, Ismail (2012)
Background: Disaster is unpredictable events and the numbers are mounting from day to day. It is crucial for nurses to be prepared in facing disaster and aftermath. The aim is to determine knowledge towards disaster management and identifying predictor factors. Methods: This comparative cross-sectional study conducted in one of states in Malaysia. The data was collected in October and November 2011. The questionnaire distributed to randomly select 468 nurses from emergency and trauma departments and health clinics with response rate of 84.6 per cent. Results: There is no difference on knowledge of both groups where 59.1% are having inadequate knowledge. Emergency nurses who attended disaster-related education/training are more likely to have adequate knowledge (p<0.05, AOR=3.807, 95% CI=1.584-9.153) and attended disaster-related education/training is predictors to the adequate knowledge of community health nurse (p<0.001, AOR=3.511, 95% CI=2.097-5.881). Conclusion: It has been proven statistically that adequacy of knowledge is driven by attending disaster-related education. Thus, it is paramount for organization to conduct disaster-related education/training as to improve knowledge towards disaster management. Keywords: disaster management; disaster nursing; emergency nurse; community/public health nurse; knowledge, attitude and practice